Design of pump performance test equipment using VDI 2221 method - Basri, Asep (Universitas Mercu Buana, 2021)
Design is a process to define something to be done using various techniques. Pumps require high stability and reliable performance, so planning and inspection of their installation must be carried out carefully and precisely. Pump performance test equipment is a tool used to test the pump performance. This study focuses on the problem of designing pump performance test equipment using the VDI 2221 method. The results obtained from this research are designing pump performance test equipment that can be used to test 2 identical pumps, namely the Shimizu PS-128BIT brand and 2 pumps that are not identical, namely the brand. Shimizu PS-128BIT with Panasonic GA-200JAK both for serial and parallel testing and in the design of the VDI 2221 method chosen, namely variant 5, (i) frame using the first model, (ii) frame material using hollow iron, (iii) water reservoir with a capacity of 1000 liters, (iv) pump 1 and pump 2 using a Shimizu PS-128BIT brand pump with a maximum discharge capacity of 18 liters/minute, (v) pump 3 using a Panasonic GA-200JAK brand pump with a maximum discharge capacity of 29 liters/minute, ( vi) the capacity of the vacuum gauge used is -76 cmHg, (vii) the maximum pressure gauge capacity is 6 Bar, (viii) the discharge capacity of the watermeter used is Qn 1.6 m^3/h, (ix) The pipe uses AW class PVC pipe with a pipe diameter of 1 inch, (x) the valve is used in the Ball model, (xi) the volumetric measuring cup with a capacity of 5 liters, and (xii) a measuring device for calculating time using a stopwatch.